Analysis of types of communication services for 6G - Simeonova, Tsvetelina (Yearbook Telecommunications, 2021)
The aim of this paper is to analyze the different types of communication services, requirements and applications related to 6G deployment, in accordance to those in 5G, and based on the definitions in the ITU recommendations. In this regard, the requirements for 6G and key performance indicators related to applications for 6G are described, arising from technological development. The results are related to obtaining summary information about the structures and features of the functioning of the various proposed communication services. Classification of the types of services in 6G has been made (new types of services in 6G, combined types of services in 6G (based on types of services in 5G), introduction of standard communication services to maintain potential scenarios for application in 6G communications). The contributions of the work are related to the in-depth analysis of the relationship between the type of services and defined requirements for 6G, presented in tabular form and conclusions are drawn.